Essay on the future: Derrida’s ethical-political thought - Bernardo, Martha Luiza (Sofia, 2025)
The present essay aims to go through some of the main quasi-concepts and articulations of Derrida's ethical-political thought that we consider as a meta-ethics and a meta-politics, since he aims not only to dramatize the concepts of traditional political theory, showing its origin, its history, its implications and performativities as, through a dissent and a refusal that we take as ultra- or hyper-political in relation to established politics, engaging in an absolutely other way of understanding the political (which also we will name a “politics of ethics”), mainly with regard to political-institutional and State policies. In this sense, we intend to point out the singularity of Derrida's ethical-political thought through the idea of ​​promise and a non-utopian impossible, the search for points of instability that permeate (or even underlie) current political and legal institutions towards their emancipation, of para-state and supra-national devices that can install a logic other than the hegemony of nation-states and that are guided by the ideas of democracy to come, in the deconstruction of state sovereignty, in the reformulation of the idea of ​​hospitality, in the proposal of a new international and another zooanthropolytics, among other topics that we will cover here.
Keywords: Derrida; ethical-political thought; deconstruction; democracy to come; hospitality